Research Progress on the Regulation Mechanism of Key Signal Pathways Affecting the Prognosis of Glioma - Wu, Hao; Wei, Min; Li, Yuping; Ma, Qiang; Zhang, Hengzhu (Frontiers in Molecular Neuroscience, 2022)
Glioma has a high malignant degree, high recurrence rate and poor prognosis. We analyzed signal pathway of the Hippo/YAP, PI3K/AKT/mTOR, miRNA, WNT/β-catenin, Notch, Hedgehog, TGF-β and the mechanism of key enzymes in glioma. It is concluded that Yap1 inhibitor may become an effective target for the treatment of glioma in the future.Inhibiting PI3K/Akt/mTOR, Shh, Wnt/β-Catenin and HIF-1α can reduce the migration ability and drug resistance of tumor cells to improve the prognosis of glioma. The analysis shows that Notch1 and Sox2 have a positive feedback regulation mechanism, and Notch4 predicts the malignant degree of glioma. In this way, notch can not only be treated for glioma stem cells in clinic, but also be used as an evaluation index to evaluate the prognosis, and provide an exploratory attempt for the direction of glioma treatment. MiRNA plays an important role in diagnosis, and in the treatment of glioma, it can play a further role with the delivery of nanoparticles and TMZ. It is believed that these studies will help us to have a deeper understanding of glioma, so that we will find new and better treatment schemes to gradually conquer the problem of glioma.